The combination of exercise training and Zataria multiflora supplementation increase serum irisin levels in postmenopausal women - Abbass Ghanbari-Niaki; Ayoub Saeidi; Mehdi Ahmadian; Leila Gharahcholo; Nooshin Naghavi; Mohammad Fazelzadeh; Soleiman Mahjoub; Stephen Myers; Andrew Williams (Integrative Medicine Research)
Background: We examined the effect of antioxidant supplementation and exercise on irisin within postmenopausal women. Methods: Forty-eight participants (age: 55.7 ± 4.9 years; weight: 68.0 ± 6.3 kg; BMI 27.0 ± 2.7; mean ± SD) were randomized into four groups for the eight week intervention: control group (CG; n = 12), resistance training group (RTG; n = 12), supplementation with Zataria multiflora group (ZG; n = 12), or supplementation with Z. multiflora and resistance training group (ZRTG; n = 12). RTG and ZRTG performed circuit resistance training, and both ZG and ZRTG consumed 500 mg of Z. multiflora every day during the intervention. Blood samples were taken 48 hours before and after the intervention. Results: There was a significant difference in irisin at post-training, with greater levels in ZRTG compared to CG. A significant increase was noted for irisin at post-training compared to pre-training for ZG, RTG, and ZRTG. Moreover, we identified a significant decrease in malondialdehyde in the RTG and ZRTG groups and increase in glutathione in the ZG, RTG, and ZRTG groups when compared to CG. Conclusion: These findings showed that exercise, Z. multiflora supplementation or their combination led to an increase in irisin. Keywords: Antioxidants, Circuit resistance training, Myokine, Postmenopausal women, Zataria multiflora